Valuing Urban Cultural Heritage in African Countries: A Contingent Valuation Study of Historic Buildings in Port Louis, Mauritius. (28th March 2019) - Bertacchini, Enrico; Sultan, Riad
Abstract: While economic valuation of cultural goods has expanded as a field of inquiry, few studies have so far focused on urban cultural heritage of African cities, places generally characterised by development pressure but also growing tourism potential. In this paper, we apply Contingent Valuation (CV) method to estimate the economic benefits arising from the preservation and rehabilitation of historic buildings in the city centre of Port Louis, Mauritius. By simultaneously analysing the preferences of both foreign tourists and local residents, the paper investigates differences of two relevant groups of users of historic city centres and discusses the challenge in assessing economic benefits to justify investments in cultural heritage preservation. Moreover, the paper adds evidence on the complex relationship between cultural attitudes toward heritage and economic valuation, revealing conditions and contexts under which the willingness to pay for cultural goods, measured by stated preference methods, might incorporate the cultural value people express on these goods.